2011
DOI: 10.1038/nchem.1151
|View full text |Cite
|
Sign up to set email alerts
|

A sequence-specific threading tetra-intercalator with an extremely slow dissociation rate constant

Abstract: A long-lived and sequence specific ligand-DNA complex would make possible the modulation of biological processes for extended periods. We have been investigating the threading polyintercalation approach to DNA recognition in which chains of aromatic units thread back and forth repeatedly through the double helix. Here we report the preliminary sequence specificity and detailed kinetic analysis of a structurally characterized threading tetraintercalator. Specific binding on a relatively long DNA strand was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Not mentioned here is our extensive work with DNA-binding oligo-NDI molecules. 74-76 Considering the complex nature of aromatic interactions, the predictable stacking geometry of DAN and NDI in water provides a well-defined recognition motif to achieve higher order architectures. Because the stacking of electrostatically complementary aromatic units is driven in part by polar solvents, the construction of aromatic foldamers and more complex aromatic assemblies in water can be more rationally designed.…”
Section: Discussionmentioning
confidence: 99%
“…Not mentioned here is our extensive work with DNA-binding oligo-NDI molecules. 74-76 Considering the complex nature of aromatic interactions, the predictable stacking geometry of DAN and NDI in water provides a well-defined recognition motif to achieve higher order architectures. Because the stacking of electrostatically complementary aromatic units is driven in part by polar solvents, the construction of aromatic foldamers and more complex aromatic assemblies in water can be more rationally designed.…”
Section: Discussionmentioning
confidence: 99%
“…By positioning the linking chain and triaminotriazine recognition units on opposite sides of the acridine unit, the bivalent complex likely requires a threading mechanism for binding (25). This design element was intentional with the goal of increasing the binding affinity through a higher residence time (26,27). …”
Section: Resultsmentioning
confidence: 99%
“…Higher DNA-binding constants, slower dissociation rates, and substantial sequence selectivity can be expected from the incorporation of two or more intercalating units into a polyfunctional ligand. 6,7 Researchers have already reported that naphthalene diimide derivatives act as DNA-targeting anticancer agents, and such derivatives have shown potent activity against cancer cell lines and telomerase. 13,14 Depending on the substituents, naphthalene diimide derivatives have shown selectivity toward AT-or GC-rich regions of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Depending on the substituents, naphthalene diimide derivatives have shown selectivity toward AT-or GC-rich regions of DNA. 4,6 We previously published our synthesis and evaluation of the binding of G-quadruplex and dsDNA with cNDI 1 and other cNDIs. 11,12 In the present study, the interaction of cNDI 1 and the newly designed cNDI 2 with dsDNA was analyzed by UV-Vis spectroscopy, CD spectroscopy, a topoisomerase I assay, and stoppedflow kinetics to characterize differences in binding mode and binding selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation